2013
DOI: 10.3906/elk-1202-24
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of emissions and exhaust temperature for direct injection diesel engine with emulsified fuel using ANN

Abstract: Exhaust gases have many effects on human beings and the environment. Therefore, they must be kept under control. The International Convention for the Prevention of Pollution from Ships (MARPOL), which is concerned with the prevention of marine pollution, limits the emissions according to the regulations. In Emission Control Area (ECA) regions, which are determined by MARPOL as ECAs, the emission rates should be controlled. Direct injection (DI) diesel engines are commonly used as a propulsion system on ships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…It provides more accurate results than the conventional statistical methods for prediction. Therefore, it has been used in different engineering applications [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It provides more accurate results than the conventional statistical methods for prediction. Therefore, it has been used in different engineering applications [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANNs can also be used in applications that require inference from existing data or completion of the missing data which make them superior to the other AI. A neural network can even improve its performance by learning new data as it becomes available [32]. Due to being a powerful tool for prediction purposes, ANN with multi-layer perceptron (MLP) structure was selected as the artificial intelligence method to predict the friction factor values obtained from experimental setup.…”
Section: Development Of the Predictive Ann Modelmentioning
confidence: 99%
“…Tab. 1 shows the input parameters that are mostly used by all authors, as well as those parameters that are found in only one of the research papers like fuel injection angle [7], inlet air temperature [8] and emulsified fuel percentages [9]. Unlike these three mentioned parameters, other input parameters are common for two, three or more research papers.…”
Section: Introductionmentioning
confidence: 99%